2018
DOI: 10.1051/matecconf/201822901010
|View full text |Cite
|
Sign up to set email alerts
|

Key performance indicators of disaster preparedness: a case study of a tsunami disaster

Abstract: Disaster impacts on human life not only in economic sector but also social, culture, and environment. In order to minimize the disaster risk, it is expected all elements who exposed to the forthcoming disaster make a good disaster preparedness then they will be resilience toward the disaster. Since individual as one of disaster stakeholder who will face a disaster directly, it is expected that they will participate actively in disaster reduction efforts. This study is aimed to design key performance indicators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…The attitude of vigilance can reduce the number of casualties due to disasters (Nasarudin et al, 2020). The attitude of vigilance in this study can be seen through indicators that include adjustment to disaster-prone areas, protection of property, and protection of life safety (Nasarudin et al, 2020;BNPB, 2018;Raja et al, 2017). This indicator has been eliminated and adjusted to the target of the research respondents.…”
Section: Disaster Alert Attitudementioning
confidence: 97%
See 1 more Smart Citation
“…The attitude of vigilance can reduce the number of casualties due to disasters (Nasarudin et al, 2020). The attitude of vigilance in this study can be seen through indicators that include adjustment to disaster-prone areas, protection of property, and protection of life safety (Nasarudin et al, 2020;BNPB, 2018;Raja et al, 2017). This indicator has been eliminated and adjusted to the target of the research respondents.…”
Section: Disaster Alert Attitudementioning
confidence: 97%
“…There are six indicators to measure community disaster knowledge: disaster characteristics, early warning systems, evacuation facilities, evacuation routes, disaster experience, and disaster simulation (Patrisina et al, 2018). Will know knowledge in this study through aspects of knowledge of landslide disasters, knowledge of mitigation measures, knowledge of early warning systems, and knowledge of evacuation routes.…”
Section: Knowledge Of Landslidesmentioning
confidence: 99%
“…Chang et al, (2016) and Tipler et al, (2017) suggest that preventive steps need to be taken earlier to avoid uncontrolled situations in managing disaster occurrences, unprepared communities have less ability to take control over the disaster event. This was supported by Patrisina et al, (2018) which mentioned that if an individual in the community is familiar and well prepared with ways of coping and precautionary measures, then the disruption by a disaster can be reduced. Furthermore, the implementation of policy and active involvement of local government in DRR enabled to mitigate the risk and potentially to increase preparedness among agencies and communities (Okada, 2012).…”
Section: Framework On Disaster Risk Reductionmentioning
confidence: 99%
“…Sutton & K. Tierney [16] and R. Patrisina et. al., [17] has listed preparedness elements, including experience, knowledge, emergency plan, and information and communication. Yenni et al, [18] has found that people's past experiences would make them more prepared and stay safe in facing flood disaster, they inherit knowledge to prepare from their parents.…”
Section: Element In Community Preparednessmentioning
confidence: 99%
“…According to R. Patrisina et. al., [17], affected people should understand the hazards and risks they will face, and they have to understand the importance of preparedness to keep safe during the disaster. Additionally, Yenni et.…”
Section: Element In Community Preparednessmentioning
confidence: 99%